Omitting cytogenetic assessment from routine treatment response monitoring in chronic myeloid leukemia is safe. (7th February 2018) - Geelen, Inge G.P.; Thielen, Noortje; Janssen, Jeroen J.W.M.; Hoogendoorn, Mels; Roosma, Tanja J.A.; Valk, Peter J.M.; Visser, Otto; Cornelissen, Jan J.; Westerweel, Peter E.
Abstract: Objectives: The monitoring of response in chronic myeloid leukemia (CML) is of great importance to identify patients failing their treatment in order to adjust TKI choice and thereby prevent progression to advanced stage disease. Cytogenetic monitoring has a lower sensitivity, is expensive, and requires invasive bone marrow sampling. Nevertheless, chronic myeloid leukemia guidelines continue to recommend performing routine cytogenetic response assessments, even when adequate molecular diagnostics are available. Methods: In a population‐based registry of newly diagnosed CML patients in the Netherlands, all simultaneous cytogenetic and molecular assessments performed at 3, 6, and 12 months were identified and response of these matched assessments was classified according to European Leukemia Net (ELN) recommendations. The impact of discrepant cytogenetic and molecular response classifications and course of patients with additional chromosomal abnormalities were evaluated. Results: The overall agreement of 200 matched assessments was 78%. In case of discordant responses, response at 24 months was consistently better predicted by the molecular outcome. Cytogenetic response assessments provided relevant additional clinical information only in some cases of molecular "warning." The development of additional cytogenetic abnormalities was always accompanied with molecular failure. Conclusion: We conclude that it is safe to omit routine cytogenetics for response assessment during treatment and to only use molecular monitoring, in order to prevent ambiguous classifications, reduce costs, and reduce the need for invasive bone marrow sampling. Cytogenetic re‐assessment should still be performed when molecular response is suboptimal.